2018
DOI: 10.1002/mma.5135
|View full text |Cite
|
Sign up to set email alerts
|

High‐order numerical solution of viscous Burgers' equation using a Cole‐Hopf barycentric Gegenbauer integral pseudospectral method

Abstract: We present a novel high-order numerical method to solve viscous Burgers' equation with smooth initial and boundary data. The proposed method combines Cole-Hopf transformation with well-conditioned integral reformulations to reduce the problem into either a single easy-to-solve integral equation with no constraints or an integral equation provided by a single integral boundary condition. Fully exponential convergence rates are established in both spatial and temporal directions by embracing a full Gegenbauer co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The following notations are used throughout this paper to abridge and simplify the mathematical formulas. Many of these notations appeared earlier in [39,44]; however, for convenience and to keep the paper self-explanatory, we summarize them below together with the new notations. Logical Symbols.…”
Section: Preliminary Notationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following notations are used throughout this paper to abridge and simplify the mathematical formulas. Many of these notations appeared earlier in [39,44]; however, for convenience and to keep the paper self-explanatory, we summarize them below together with the new notations. Logical Symbols.…”
Section: Preliminary Notationsmentioning
confidence: 99%
“…We refer to Θ 2π by the "basic/principle" FIM, because of its simplest form, the "generating" FIM due to Formula (4), or the "natural" FIM, since its merits place it as the natural choice among all possible FIMs. For further information about FPS interpolation and quadratures, the reader may consult the recent works [39,42,44].…”
Section: Fps Interpolation and Quadraturementioning
confidence: 99%
See 1 more Smart Citation
“…The current methods do not suffer from this limitation, as they generally remain stable for large mesh grids and certain parameter ranges, as we will demonstrate later in Sections 5 and 9. For a comprehensive review on IPS and IS methods, the reader may consult [7][8][9][10][11][12][13], and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review on recent progress on Fourier PS methods can be found in [2,[16][17][18][19]. For a survey on Gegenbauer polynomials and quadratures and their relevant theory, the reader may consult [13,[20][21][22][23], and the references therein.…”
Section: Introductionmentioning
confidence: 99%